Hubungan antara Intensitas Penggunaan Media Sosial Instagram dengan Tingkat Kebahagiaan Remaja - 10080021146, Fauzan Ridha Muhammad; Zulfebriges (Bandung Conference Series: Public Relations, 2025)
Abstract. provides space for its users to share, interact, and access various types of content, including family content as presented by @fadiljaidi account. This study uses a correlational quantitative approach with a sample of 93 students of the Faculty of Communication Sciences, Islamic University of Bandung (FIKOM UNISBA) who are active Instagram users and followers of the @fadiljaidi account. The independent variable in this study is the intensity of Instagram use measured through four indicators, namely: frequency, duration, attention, and appreciation. Meanwhile, the dependent variable is the level of adolescent happiness which includes the dimensions of positive emotions, involvement, meaning, positive relationships, and achievement. Data analysis was conducted through descriptive statistical tests and Rank Spearman correlation with the help of SPSS software version 25 and a significance level of 0.05. The results showed that there is a significant positive relationship between the intensity of Instagram use and the level of adolescent happiness, with a significance value of 0.000 and a correlation coefficient of 0.518 which is included in the strong category. Each indicator of intensity of use (frequency, duration, attention, appreciation) shows a relationship with the level of adolescent happiness. Positive, warm and entertaining family content such as @fadiljaidi's can improve adolescents' psychological well-being by encouraging emotional reflection, healthy social interactions and feelings of emotional connectedness. Abstrak. Instagram sebagai salah satu platform digital yang paling populer di kalangan remaja, memberikan ruang bagi penggunanya untuk berbagi, berinteraksi, dan mengakses berbagai jenis konten, termasuk konten keluarga seperti yang disajikan oleh akun @fadiljaidi. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan sampel sebanyak 93 mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung (FIKOM UNISBA) yang merupakan pengguna aktif Instagram dan pengikut akun @fadiljaidi. Variabel bebas dalam penelitian ini adalah intensitas penggunaan Instagram yang diukur melalui empat indikator, yaitu: frekuensi, durasi, perhatian, dan penghayatan. Sementara itu, variabel terikat adalah tingkat kebahagiaan remaja yang mencakup dimensi emosi positif, keterlibatan, makna, hubungan positif, dan prestasi. Analisis data dilakukan melalui uji statistik deskriptif dan korelasi Rank Spearman dengan bantuan software SPSS versi 25 dan tingkat signifikansi 0,05. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara intensitas penggunaan Instagram dan tingkat kebahagiaan remaja, dengan nilai signifikansi sebesar 0,000 dan koefisien korelasi 0,518 yang termasuk dalam kategori kuat. Setiap indikator intensitas penggunaan (frekuensi, durasi, perhatian, penghayatan) menunjukkan adanya hubungan dengan tingkat kebahagiaan remaja. Konten keluarga yang bersifat positif, hangat, dan menghibur seperti milik @fadiljaidi mampu meningkatkan kesejahteraan psikologis remaja dengan mendorong refleksi emosional, interaksi sosial yang sehat, dan perasaan terhubung secara emosional.